Highly Conductive Nitrogen‐Doped sp2/sp3 Hybrid Carbon as a Conductor‐Free Charge Storage Host. (3rd November 2022) - Wang, Qi; Su, Jincang; Chen, Hailun; Wang, Deqiang; Tian, Xiaoyu; Zhang, Yujian; Feng, Xin; Wang, Shun; Li, Jun; Jin, Huile
Abstract: It is commonly accepted that the increased degree of graphitization leads to a higher electrical conductivity of carbon materials. However, more and more evidence reveals that heteroatom doping on carbon host can also improve the conductivity, owing to the dopant atoms contributing to higher charge delocalization and density of donor states near Fermi level. The reality is, such conductivity improvement from doping is often overwhelmed by graphitized carbon. Although heteroatom‐doped carbon is widely used as active materials in the fields of energy storage and electrocatalysis, which still requires extra carbon‐based conductive additives to enhance the overall conductivity. In this stu, it is demonstrated that the electrical conductivity of finely designed nitrogen‐doped carbon is even beyond the commercialized carbon conductors over 3.5 times, endowing such conductive agent‐free electrode material an excellent performance in an all‐solid‐state flexible supercapacitor. The theoretical simulation further demonstrates that N‐doped sp 2 /sp 3 hybrid carbon can migrate the Fermi level to the conduction band, leading to an n ‐type conductivity due to the additional electrons caused by the N dopant. Abstract : This report provides a kind of highly conductive nitrogen‐doped carbon as a conductor‐free charge storage host for high‐performance flexible supercapacitors. Such highly conductive heteroatom‐doped carbon materials should be attractive by their bi‐functionalities, to be simultaneously as active centers and conductive agents in many other energy storage and conversion systems.